Exploring Postgraduate Students’ Lived Experiences in Extensive English Reading Courses: A Phenomenology Study at One Public University in Jambi - Khairunnisa, Siti; Abrar, Mukhlas Abrar; Arif, Nely Arif (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores postgraduate students' lived experiences in the newly introduced Extensive English Reading course at a state university in Jambi as part of the English education curriculum revision. The objective is to understand students' challenges, strategies, and reflections using a qualitative phenomenological approach. The population comprised Master's in English Education students in 2024, with a purposive sample of three second-semester female students. Instruments included semi-structured interviews and reflective journals, analyzed via Braun and Clarke's (2006) thematic analysis. Findings revealed three themes: linguistic challenges, workload, and low motivation; cognitive, metacognitive, and social strategies; and positive reflections with greater need for instructor support. The conclusion emphasizes the necessity of accessible texts and active teacher guidance to optimize Extensive Reading implementation.